ANALYSIS OF THE REAL AND THE IDEAL LEADERSHIP PROFILES IN CAPOEIRA (Fiep Bulletin - online, 2015)
The revision of the literature on sports reveals that the coach's and teacher's leadership behaviors have been frequently studied and are seen as important aspects for performance and satisfaction. Thus, the present study had the objective of analyzing the leadership profile of the capoeira master in relation to the master's self-perception and also in relation to the students' perception and preference. A group of 26 male and female capoeira players aged 28.15 (±8.11) on average and with 79 (±71.32) months of capoeira practice time and different grades in accordance with the evaluated group's hierarchy. A demographic and a Leadership Scale for Sport  LSS questionnaires (perception, preference, and self--perception) was used as a survey tool. In general, the leadership styles most perceived by the students were democratic behavior and positive feedback. The students preferred mostly the democratic behavior and Training-Instruction behavior styles. The master reported self-perceived democratic and Training-Instruction behaviors. The comparison of the three LSS versions showed statistical differences only for positive feedback (p=0.03) and Training-Instruction (p=0.02) dimensions. It can be concluded that the master presents decision making and interaction styles in agreement with the students' preference and perception. This leads us to conclude that this similarity is a predictor of efficacy and effective leadership.
Keywords: capoeira master; leadership style; students perception / preference